Effects of foreign share markets on the Malaysian share market. - Kilicman, Adem; Subramaniam, Melissa (European Journals, Inc., 2011)
This research is carried out to study the effects of the foreign share market towards the Malaysian share market using method of least squares in SPSS. Thus, a total of 450 historical data representing four of the largest export trade partners namely the United States (U.S), Singapore, Japan and China had been selected to be used in predicting the opening price of KLSE share price. In addition, we want to gain a better understanding on the effects of these export trading partners based on two different aspects, the geographical aspect and the impact of giant share markets. As a result of this study, it was found that the least square method can predict the stock price movement. In addition, we also noticed that out of the final eight variables that were included in the suggested linear regression model, STI-OPN (Singapore) is highly significant. Thus, result of this research disagrees with the general conception that the U.S market is playing a big role in determining the Malaysian share market.